Star wars. A new hope [videorecording (Blu-Ray)] - Lucas, George, 1944-; Hamill, Mark; Ford, Harrison, 1942-; Fisher, Carrie; Guinness, Alec, 1914-2000 (LucasFilm, 2019)
Luke Skywalker begins a journey that will change the galaxy. Nineteen years after the formation of the Empire, Luke is thrust into the struggle of the Rebel Alliance when he meets Obi-Wan Kenobi, who has lived for years in seclusion on the desert planet of Tatooine. Obi-Wan begins Luke's Jedi training as Luke joins him on a daring mission to rescue the beautiful Rebel leader Princess Leia from the clutches of Darth Vader and the evil Empire.